Single and multi-channel passive source methods for calculating the shallow S-wave velocity structure and site effect parameters at 15th May City, Egypt. (November 2019) - Abudeif, A.M.; Mohammed, M.A.; Abd el-aal, A.K.; Omar, Kh.A.
Abstract: In this work, two passive seismic techniques were utilized for recording noise data at 57 sites to estimate near-surface soil response in 15th May city. Single seismic station of microtremor data was used to investigate the study area utilizing Nakamura method of Horizontal to Vertical Spectral Ratio (HVSR) to determine the structure in terms of the predominant frequency. At each point of microtremor measurement, the natural frequency and amplification factor were estimated. Velocities of transverse waves (VS ) of the upper part section of the sedimentary succession are estimated using microtremor observations technique. The spatial autocorrelation (SPAC) method was employed for estimation dispersion curves, VS structure was resulting by genomic algorithm. The results demonstrate that, the fundamental resonance frequency is varying from 1.36 Hz to 1.607 Hz at the majority of the study area, amplification values ranges between 1.09 and 3.61 and the thickness of unconsolidated sediments were determined. The retrieved shear-wave velocity models were characterized by significant impedance contrasts for array site № 1 at 7 m, 13 m, and 36 m depths corresponding to velocities 142, 636 and 1047 m/s, array site № 2 at 2 m, 6 m, and 16 m depths corresponding to velocities 253, 614 and 942 m/s and array site № 3 at 2 m, 6 m, and 20 m depths corresponding to velocities 242 m/s, 608 m/s and 1027 m/s respectively. Value results of F o were used in the calculation of bedrock depth at the measured sites. The parameters obtained in this study are matching well with the site geology. Based on the average shear wave velocity values for the top 30 m (VS 30) for each array location, the site classes were estimated. The sites Ar_1 and Ar_2 belong to class C (very dense soil and soft rock), while Ar_3 fit in class B (rock). Highlights: VS values of the sedimentary succession were evaluated using microtremor technique. Passive techniques are valuable tool for soil type evaluation using VS estimation. The amplification factor increases when thickness of the sediments increases. The resonance frequency becomes high when bedrock depth is shallow and vice versa. Array sites 1 and 2 belong to class C (very dense soil) while 3 is class B (rock).